Marketing Communication Strategy of Fruit Vendors in the Purwodadi Traditional Market in the Era of Increasing Online Fruit Sellers - Tika, Yori Manis; Levy Oktridarti; Hania Sumarni; Heni Indriani; Imron Rosyadi; Fanro (Journal of Social Science and Humanities, 2025)
The rise of digital technology and the increasing use of online selling platforms have significantly transformed consumer purchasing behavior, including the purchase of fresh fruits. Fruit sellers in the Purwodadi Traditional Market face substantial challenges in retaining customers and increasing purchase interest amid intense competition with online fruit vendors. This study aims to analyze the marketing communication strategies employed by traditional fruit sellers in response to consumer behavior shifts in the digital era. Using a descriptive qualitative approach, data were collected through in-depth interviews, direct observations, and documentation involving fruit sellers, buyers, and vendors who also utilize online platforms. The results indicate that verbal and nonverbal face-to-face communication remains the most effective strategy in building trust and emotional closeness with consumers. Sellers have also begun adapting by implementing simple promotional strategies, such as onsite discounts and product updates via WhatsApp Story. Furthermore, service quality is a key differentiator compared to online vendors. However, traditional sellers still encounter challenges related to digital marketing skills, price competition, and limited use of online tools. The study concludes that combining interpersonal communication with basic digital promotional strategies can effectively enhance the competitiveness of traditional market sellers.